2013
DOI: 10.1186/1477-7525-11-181
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated quality of life of city-dwelling elderly people benefitting from social help: results of a cross-sectional study

Abstract: BackgroundThe percentage of people aged 65 or older living in Poland is 13.6%, but 17.2% in Łódź. The aim of the study was to identify factors correlating with the self-rated quality of life of elderly inhabitants of cities applying for social help, on the basis of a cross-sectional study.MethodsThe study was conducted in Łódź, a large Polish city, between September 2011 and February 2012 in a group of people applying for help in the Municipal Social Welfare Centre. Four hundred and sixty-six respondents aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
31
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 43 publications
11
31
0
3
Order By: Relevance
“…Araújo et al (2010) concluded that these differences may indicate distinct differences in the way oral health is perceived upon quality of life at different ages or stages in life (15). Bryla et al (2013) demonstrated that age on its own was not a determining factor but when combined with other variables such as diseases as well as mental and physical disabilities it could significantly decrease quality of life. In the current study, all subjects were systemically healthy with no mental or physical disabilities and this may explain the lack of an association between age and OHQoL (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Araújo et al (2010) concluded that these differences may indicate distinct differences in the way oral health is perceived upon quality of life at different ages or stages in life (15). Bryla et al (2013) demonstrated that age on its own was not a determining factor but when combined with other variables such as diseases as well as mental and physical disabilities it could significantly decrease quality of life. In the current study, all subjects were systemically healthy with no mental or physical disabilities and this may explain the lack of an association between age and OHQoL (25).…”
Section: Discussionmentioning
confidence: 99%
“…Bryla et al (2013) demonstrated that age on its own was not a determining factor but when combined with other variables such as diseases as well as mental and physical disabilities it could significantly decrease quality of life. In the current study, all subjects were systemically healthy with no mental or physical disabilities and this may explain the lack of an association between age and OHQoL (25). Fernandes et al (2006) found the impacts on OHQoL of patients who were smokers to be higher than non-smokers (22).…”
Section: Discussionmentioning
confidence: 99%
“…A survey carried out with Polish elders found that in order to have a high quality of life, it is necessary to have good education and sufficient income to live (43) . Therefore, it is important to consider that, in health care for elderly women, social determinants, such as income and level of education, contribute to quality of life and consequently to a positive perception of health.…”
Section: Discussionmentioning
confidence: 99%
“…Unsatisfactory health state is connected with being Afro-American ethnicity, age, obesity, smoking nicotine, low income, place of residence and low level of education [20][21]. It is also very important to undertake appropriate health policy decisions aiming at the improvement of research capacities of many European countries [22].…”
Section: Discussionmentioning
confidence: 99%